2016
DOI: 10.1210/en.2015-1768
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Sphingosine 1-Phosphate Receptor 2 Signaling Attenuates High-Fat Diet-Induced Adipocyte Hypertrophy and Systemic Glucose Intolerance in Mice

Abstract: Sphingosine 1-phosphate (S1P) is known to regulate insulin resistance in hepatocytes, skeletal muscle cells, and pancreatic β-cells. Among its 5 cognate receptors (S1pr1-S1pr5), S1P seems to counteract insulin signaling and confer insulin resistance via S1pr2 in these cells. S1P may also regulate insulin resistance in adipocytes, but the S1pr subtype(s) involved remains unknown. Here, we investigated systemic glucose/insulin tolerance and phenotypes of epididymal adipocytes in high-fat diet (HFD)-fed wild-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(68 citation statements)
references
References 38 publications
2
65
1
Order By: Relevance
“…Insulin resistance has been proven as a critical factor that links metabolic diseases to obesity [Kitada et al, 2016]. Insulin resistance has been proven as a critical factor that links metabolic diseases to obesity [Kitada et al, 2016].…”
Section: Discussionmentioning
confidence: 99%
“…Insulin resistance has been proven as a critical factor that links metabolic diseases to obesity [Kitada et al, 2016]. Insulin resistance has been proven as a critical factor that links metabolic diseases to obesity [Kitada et al, 2016].…”
Section: Discussionmentioning
confidence: 99%
“…Muscle‐related insulin resistance caused by ceramide could be prevented by sphingosine kinase 1 (SK1), in part by promoting sphingosine incorporation into sphingosine‐1‐phosphate (S1P), but not into Cer (which is composed of sphingosine and fatty acid) . A recent study found that blockade of S1P receptor 2 signaling attenuated adipocyte hypertrophy and systemic glucose intolerance in mice fed an HFD . Without insulin being secreted, there is an absence of lipolysis suppression, which increases plasma free fatty acid (FFA) levels .…”
Section: Discussionmentioning
confidence: 99%
“…41 A recent study found that blockade of S1P receptor 2 signaling attenuated adipocyte hypertrophy and systemic glucose intolerance in mice fed an HFD. 42 Without insulin being secreted, there is an absence of lipolysis suppression, which increases plasma free fatty acid (FFA) levels. 43,44 Fox et al 45 showed that plasma levels of a bioactive sphingolipid metabolite formed by the phosphorylation of sphingosine, namely S1P, were markedly elevated, whereas levels of ω9 24:1 acid (nervonic acid) were reduced in T1DM rat models with concomitant decreases in plasma concentrations of 24:1-esterified sphingolipids (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Levels of plasminogen activator inhibitor-1, which is produced from adipocytes, are increased in obese individuals. Interestingly, JTE-013 suppressed plasminogen activator inhibitor-1 increases in mouse 3T3-L1 adipocytes (Ito et al ., 2013), and S1P 2 deficient mice fed a high-fat diet had better glucose/insulin tolerance test results and smaller epididymal adipocytes (Kitada et al ., 2016). These results suggest JTE-013 might be useful for treating obesity and type 2 diabetes.…”
Section: Development Of S1p Receptor Antagonistmentioning
confidence: 99%